(untitled) (Al-Qamar, 2022)
Dr. Sayed Muhammad al-Tantāwī is one of the prominent scholars. He was late Sheikh of Al-Azhar 1996 AD to 2010 AD. He was known for his moderate Islamic thought, which combine tradition and modernity. He played a prominent role in reforming Muslim society by mitigating intolerance hatred and ignorance. He was a great preacher and authors. He authored ‘’ Tafsir al–Vasīt”, which is modern Tafsir that contains specific role for proper methodology of dawah. In this paper the researcher tries to uncover the Attributes of a preacher from the mentioned Tafsīr.